Analysis of time-dependent seismic fragility of the offshore bridge under the action of scour and chloride ion corrosion. (December 2020) - Li, Tinghui; Lin, Junqi; Liu, Jinlong
Abstract: This study uses the time-dependent fragility analysis method, based on the Duracrete model and previous experimental results, to determine the probability distribution types and statistical characteristics of various environmental parameters and corrosion parameters. In this paper, an analysis framework is proposed to study the seismic fragility of bridges under the action of chloride ion corrosion and scour. With the increase of scour depth, the seismic fragility of the bridge in the example shows nonlinear growth, and the fragility of the laminated rubber bearing is higher than that of the pier, which makes the laminated rubber bearing sustain more significant damage than the pier when the earthquake occurs, thus playing the role of a "fuse" and reducing the seismic damage of the pier. Based on the Duracrete model, the degradation law of reinforced concrete performance with time was obtained by the Monte Carlo method under a chloride ion corrosion environment. Compared with the apparent increase of bridge pier fragility, the fragility change of the laminated rubber bearing was not noticeable and showed a trend of increasing first and then decreasing. Under the combined action of chloride ion corrosion and scour, the seismic fragility of the laminated rubber bearing in the early service stage of the bridge is dramatically higher than that of the pier, which leads to the laminated rubber bearing being damaged before the pier to protect the pier in the case of an earthquake. With the increase of service time, the seismic fragility of the pier is gradually higher than that of the laminated rubber bearing, which becomes a weak link in the anti-seismic system of bridges.